Regulation of influenza virus infection by microRNAs - Zhong ZOU; Wen-xiao GONG; Kun HUANG; Xiao-mei SUN; Mei-lin JIN (Journal of Integrative Agriculture)
MicroRNAs (miRNAs) are small noncoding RNAs of 18–25 nucleotides (nt) in length that represent key regulators of many normal cellular functions through the inhibition of mRNA translation and mRNA degradation. To date, over 2 500 mature miRNAs have been identified in plants, animals and several types of viruses. Influenza A virus (IAV), which is a negative-sense, single-stranded RNA virus, does not encode viral miRNA. However, IAV infection can alter the expression of host miRNAs, either in cell culture or in host. In turn, host miRNAs regulate IAV life cycle through directly binding to IAV genome or indirectly targeting host factors associated with viral replication. In this review, we briefly summarized the role and significance of miRNA in relation to IAV pathogenesis. Understanding the role of cellular miRNAs during viral infection may be beneficial to the identification of novel therapeutic strategies to block IAV replication.